A new species of Dune Cricket from China (Orthoptera: Ensifera: Schizodactylidae) - He, Zhu-Qing; Liu, Yi-Jiao (Zootaxa, 2021)
A new species, Schizodactylus jimo He sp. nov., is described from Yunnan, China. The Schizodactylidae is recorded from China for the first time. The new species is similar to S. salweenensis, but different based on the shape of epiproct and other characters. The type specimens are deposited in the Museum of Biology, East China Normal University (ECNU).